POLYTYPE DIVERSITY OF THE HYDROTALCITE-LIKE MINERALS II. DETERMINATION OF THE POLYTYPES OF EXPERIMENTALLY STUDIED VARIETIES - Bookin A.S.; Cherkashin V.I.; Drits V.A. (My University, 1993)
Polytype diversity of hydrotalcite-like minerals is mainly a function of the nature of the interlayer anion. Among the varieties with COl- anions, only two- and three-layer polylypes having the same structure as manasseite and hydrotalcite have been confirmed. Stichtite and reevesite, which have been previously identified as six-layer polytypes, are in fact three-layer polytypes. Among SO4 ~ varieties, one-layer and three-layer polytypes have been identified, but the one-layer types are only present in more hydrated minerals with larger interlayer spacings. The three-layer varieties are of three different polytypes, with both P- and O-types ofinterlayers. Both rhombohedral and hexagonal varieties exist. Interlayer type may change during hydration-dehydration or anion exchange. Thus, in contrast with the COs2--bearing minerals, a complete description of the polytype of the SO42--bearing minerals cannot be made by simply indicating the number of the brucite-like layers in the unit cell. The two-layer unit cell seen in refined crystal structures of some minerals with SO42- interlayers is not due to a doubled periodicity of alternation of brucite-like layers but to periodicity of interlayer anions, or layer cations.
Keywords: Hydrotalcite-like group; Polytype; X-ray diffraction criteria